Princess : a true story of life behind the veil in Saudi Arabia - Sasson, Jean P. (Van Nuys, CA : Windsor-Brooke Books, 2001)
A Saudi woman discusses what life is like for women in her country, describing how women are sold into marriage to men five times their age, are treated as their husbands' slaves, and are often murdered for the slightest transgression.
Childhood -- Family -- My sister Sara - Divorce -- Ali -- Trip -- Journey's end -- Girlfriends -- Foreign women -- Huda -- Kareem -- Wedding -- Married life -- Birth -- Dark secrets -- Death of a king -- Woman's room -- Second wife -- Escape -- Great white hope -- Epilogue -- Afterword -- Appendices: Koran on women -- Laws of Saudi Arabia -- Glossary -- Chronology -- Index.
Includes index.
Keywords: Sultana, -- 1956-; Women -- Saudi Arabia -- Social conditions; Princesses -- Saudi Arabia -- Biography; Women -- Saudi Arabia -- Social conditions; Princesses -- Saudi Arabia -- Biography